Inwestycje portfelowe a rozwój i komercjalizacja systemu finansowego w Chinach - Rosińska, Magdalena (Portfolio Investment as an Impact for Development and Commercialization of Financial System in China, 2008)
The Chinese economy is a very important and interesting topic for an analysis because of its high rate of GDP increase (about 10.5%). The main source of financial means was always the contribution of the government, but now individual investments (also foreign) and companies are becoming more and more important. This causes development and commercialization of financial system. It is very important to see the financial system as a totality. We can look at it also as all financial institutions, as banks, stock exchanges or insurance associations. They are connected with each other and all represent private or state interests. Foreign investments, especially portfolio investments on Chinese stock exchanges, become the positive signal for development. They have influence on all elements of financial system. They give Chinese people signal to save financial means and the way to earn on it, Chinese companies have money for investing and building new plants in different countries. The Chinese economy becomes the most important at global market, also financial. There are some mistakes which have to be reduce to make the Chinese financial system more effective. People must believe in safety of investing, so new financial institutions must arise. With good involvement of state policy, companies can find foreign investors on domestic stock exchanges and compete on global markets. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 28, s. 202-212